Indonesian transnational female domestic workers: Between agency and the commodification of love and care - Irawaty, Diah (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2022)
The decision for being migrant domestic workers among Indonesian mothers often creates a dilemmatic situation for them. On the one hand, they really want to secure and save their family’s economy and support their children’s education. However, on the other hand, leaving their children in the home country for a long period of time produces a guilty feeling; in fact, they are stigmatized as irresponsible and bad mothers. This article discusses how the experiences of transnational migration among Indonesian mothers for being domestic workers abroad contribute to diversify the meanings and practices of motherhood, including mother-child relations. In this study, ten participants were interviewed and asked how the transnational migration enables them to reconstruct the traditional norms, structures, patterns, and arrangements of motherhood. The studies on new motherhood among migrant mothers reveal two distinctive conceptualizations of motherhood and parenthood that center in the role of sending money and gifts, which are the emotionalization of money and the commodification of love. This article elaborates dynamic and heterogenous reasons of being engaged in the commodification and commercialization of love and care among transnational mothers. I argue that through their consumption practices and behavior, Indonesian migrant domestic workers re(produce), negotiate and maintain their personal, familial, and social relationships with their children and their society to fit their motherhood role into accepted social expectations due to their physical absence.